Sowing Quality of Asparagus officinalis L. Hybrid Seeds After Low-Temperature and Hydrothermal Treatment - Lialiuk , Olga; Ivchenko , Tetiana; Shevchenko, Nadiya; Stribul , Tamara (Problems of Cryobiology and Cryomedicine, 2020)
Probl Cryobiol Cryomed 2020; 30(3): 289